THE 2004 BANKING SECTOR REFORMS IN NIGERIA AND FUNDING CHALLENGES TO SMES: SHARING THE CULPABILITY BETWEEN LENDERS AND BORROWERS - OBIANAGWA, CHRISTOPHER EWUZIE; EZE, NKIRU UCHEDILICHUKWU (JOURNAL OF ECONOMICS AND ALLIED RESEARCH, 2020)
The beginning of Nigeria’s Fourth Republic in 1999 was characterized by reforms that led to the overhaul of both public and private sectors of the economy under the NEEDS programme. While the Nigerian banks have improved in performance and operations following the 2004 reforms, the effect has not been felt significantly by the Small and Medium scale Enterprises (SMEs). The study examined both internal and external factors constraining SMEs’ access to bank loan. We relied on the qualitative data collected through primary sources such as interviews, and secondary sources such as scholarly works, official documents, and media reports; and were analyzed descriptively. The study revealed that high interest rates have adverse effects on the SMEs. Also, the study found among others that circumvention of banks by most SMEs in their business and financial transactions is a barrier to accessing bank loans. We recommended inter alia that the CBN should review lending rates to SMEs with a view to ensuring that loan rates, moratorium and loan tenure are complementary and designed to support business profitability, continuity and expansion while comprehensive enlightenment programmes should be developed to educate SME operators on the critical need to use banks for their business and financial transactions.